2021
DOI: 10.1007/s00405-021-06881-8
|View full text |Cite
|
Sign up to set email alerts
|

Driving ability in patients with dizziness: a systematic review

Abstract: Introduction-Dizziness is considered one of the most common symptoms in general medical practice. Patients can suffer from a wide range of symptoms that are highly relevant while driving and may affect driving ability. In most countries driving restrictions have been suggested for patients with dizziness or a vestibular disorder. However, these restrictions are not always evidence-based and differ significantly between European countries.Objective-The aim of this systematic review was to identify and evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Medication, dizziness and drowsiness were discussed with those patients prescribed medication, improving patient awareness and possibly the safety of all road users. 7,8,21,26 Most people with dizziness and imbalance described their symptoms as predictable (e.g. the symptoms only occurred when the individual performed certain movements, or they had a warning sign), controllable (not severe enough to be disabling), or both predictable and controllable, following shared decision-making discussions 32 to explore these parameters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Medication, dizziness and drowsiness were discussed with those patients prescribed medication, improving patient awareness and possibly the safety of all road users. 7,8,21,26 Most people with dizziness and imbalance described their symptoms as predictable (e.g. the symptoms only occurred when the individual performed certain movements, or they had a warning sign), controllable (not severe enough to be disabling), or both predictable and controllable, following shared decision-making discussions 32 to explore these parameters.…”
Section: Resultsmentioning
confidence: 99%
“…19 However, given its importance, the topic of driving and dizziness or vertigo should always be addressed in those presenting with these symptoms, 20 and in patients taking medication that causes dizziness or drowsiness, 20 as data are consistent regarding the effects of medications used for dizziness and vertigo on driving ability. [6][7][8][9][10][21][22][23] Vestibular disorders have been shown to negatively affect driving ability in most studies, with a low risk of bias, 16,17,22 and any associated anxiety or mood disordersprevalent in vestibular disordersmay also affect driving. 16 A systematic review revealed a significant heterogeneity in studies reporting driving performance, with contradictory results, 21 which makes giving accurate, condition-specific advice more challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conceptual framework is centered around the full spectrum of BVP symptoms and categorizes them in three different domains: the physical, cognitive, and emotional domain. The burden of these symptoms increases when performing certain activities such as cycling or driving a car, leading to limitations in carrying out these activities ( 47 ). Consequently, patients show altered behavior such as slowing down or paying more attention while performing activities or even avoiding specific activities ( 6 ).…”
Section: Conceptual Model and Contextmentioning
confidence: 99%
“…For instance, an increase in vestibular symptoms while car driving was reported in 56% of these patients (Lucieer et al 2020). Several studies assessed driving abilities in persons with dizziness and vestibular dysfunction, showing its detrimental effect on self-reported driving ability and the occurrence of car accidents (Uwents et al 2021). Although 94% of persons with BV report an increase of symptoms while cycling, detailed studies about cycling abilities in this population are lacking (Lucieer et al 2020).…”
Section: Introductionmentioning
confidence: 99%